Etika Periklanan Pada Media Sosial Instagram di Era Influencer - Azharia; Novitasari, Adinda Wulan; Priyanda, Adinda Bagesa; Handoko, Daniel (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2024)
The development of social media such as Instagram has transformed advertising paradigms with the emergence of influencer marketing. Influencers play a crucial role in shaping consumer opinions and behaviors, leveraging their trust and credibility to promote products in a personal and authentic manner. However, this practice also faces ethical challenges, particularly regarding transparency in marking sponsored content. Regulations and platform initiatives have been introduced to enhance transparency, yet understanding and compliance remain significant issues. This study highlights the need for stricter guidelines and education for influencers to ensure more ethical advertising practices in today's digital age. Keywords: Advertising Ethics; Social Media; Instagram; Influencer